Induction hardening of steels with use of the device for incremental forming of round bars HDQT-R 30-12. (January 2020) - Peković, M; Vrtáček, J; Janda, T; Volkmannová, J
Abstract: Induction hardening is mainly used for treating parts in which high hardness, wear-resistance, and ductile core are required, such as spur gears, wind turbine rings, and bearings. Innovative induction hardening processes are also developed for complex automotive components, such as camshafts and crankshafts. In the process, steel is heated by passing high-frequency alternating current through a coil which is equivalent to the primary winding of a transformer. The material to be heat-treated is equivalent to a short-circuited secondary winding. The HDQT-R 30-12 device for incremental forming of round bars includes modules which can be used for heat-treating bars after rolling or even without rolling. Heating is provided by five induction coils at a faster rate than in a chamber furnace. In addition, there is less oxidation of the material surface. This paper presents findings related to microstructures and hardnesses in 42CrMo4, 13CrMo4, and S235JR steel grades after heating at different inductor coil power settings with subsequent hardening in a water bath.